Interpret the initial value problem
"{d^2 \\theta \\over dt^2}+\\beta^2\\theta=0, \\ \\theta(0)=\\theta_0,\\ {d\\theta \\over dt}(0)=\\omega_0" Use the notation
"{d^2 \\theta \\over dt^2}=\\theta'',\\ {d \\theta \\over dt}=\\theta'" We get
"\\theta''+\\beta^2\\theta=0" The auxiliary equation is "r^2+\\beta^2=0" or "r^2=-\\beta^2," whose roots are "\\pm i\\beta."
The general solution is
"\\theta(t)=c_1 \\cos(\\beta t)+c_2\\sin(\\beta t)" Then
"\\theta'=-\\beta c_1\\sin(\\beta t)+\\beta c_2\\cos(\\beta t)" The initial conditions become
"\\theta(0)=c_1=\\theta_0"
"\\theta'(0)=\\beta c_2=\\omega_0=>c_2={\\omega_0 \\over \\beta}" Hence
"\\theta(t)=\\theta_0 \\cos(\\beta t)+{\\omega_0 \\over \\beta}\\sin(\\beta t)"
Spring system
"\\begin{matrix}\n x & displacement \\\\\n dx\/dt & velocity \\\\\n m & mass \\\\\n c & damping\\ constant \\\\\n k & spring\\ constant \\\\\n F(t) & external\\ force\n\\end{matrix}"If we ignore any external resisting forces (due to air resistance or friction) then, by Newton’s Second Law (force equals mass times acceleration), we have
"m{d^2 x \\over dt^2}=-kx" Or
"{d^2 x \\over dt^2}+{k\\over m}x=0"Let "\\beta^2=\\dfrac{k}{m}." Then the solution of the initial value problem
"{d^2 x \\over dt^2}+\\beta^2x=0, \\ x(0)=x_0,\\ {dx\\over dt}(0)=v_0" is
"x(t)=x_0 \\cos(\\beta t)+{v_0 \\over \\beta}\\sin(\\beta t), \\beta=\\sqrt{{k \\over m}}"
Comments
Leave a comment